Phytochemical screening, antioxidant, and antimicrobial analysis of Portulaca oleracea seeds with in-silico molecular docking insights - Khursheed Ahmad Sheikh; Reyaz Hassan Mir; Mohammad Ovais Dar; Adil Farooq Wali; Insha Qadir; Sheeba Nazir; Mohammed Iqbal Zargar; Sirajunisa Talath; Sathvik B. Sridhar; Javedh Shareef; Mubashir Hussain Masoodi (Journal of Genetic Engineering and Biotechnology)
Background: Portulaca oleracea (PO), an annual succulent herb with global distribution, has been used medicinally since ancient times, earning the title “global panacea.” Aim: This study aimed to perform phytochemical screening, antioxidant and antimicrobial analysis of PO seeds, including GCMS analysis of methanolic extract and molecular docking for antimicrobial mechanisms. Materials and Methods: PO seeds underwent phytochemical screening and methanolic extract analysis via DPPH, NO radical scavenging, and reducing power assays. Antimicrobial activity was tested against bacteria and fungi, with GCMS identifying compounds. Molecular docking was conducted via Autodock vina, against targets beta-tubulin (5FNV) and ABC transporter (6J9W). Results: Methanolic extract showed strong antioxidant activity (IC50: 125.2 µg/ml for DPPH, 402.89 µg/ml for NO) and concentration-dependent reducing power. It was highly effective against Saccharomyces cerevisiae and Hypochrea viridescens. GCMS identified colchicine, n-decanoic acid, and triepoxydecane, with colchicine showing high binding affinity to protein targets. Conclusion: The methanolic extract’s potent antioxidant and antimicrobial effects, supported by colchicine’s binding affinity, validate PO’s medicinal potential, suggesting further therapeutic exploration.